NEW POSSIBILITIES OF SURGICAL CORRECTION OF POP WITH USE OF SYNTHETIC IMPLANTS: WAYS OF PREVENTIVE POSTOPERATIVE COMPLICATIONS - V. F. Bezhenar; E. V. Bogatyreva; A. A. Tscipurdeeva; L. K. Tsculadze; E. I. Rusina; E. S. Guseva (IRBIS LLC, 2016)
Per-operative and post-operative complications of polypropylene mesh surgery with synthetic systems are characterized in this article. The methods of complications prevention and management are described.